TRAINING AT EDUCATION CLUSTER: QUALITY ASSESSMENT MODEL - Sergey A. Kogogin; Liliya R. Yagudina (Высшее образование в России)
The article describes the theoretical and methodological approaches to assessment of quality training at education cluster. The authors present the experience in designing and implementing an integrated model of quality assessment in engineering education cluster. Education ideology and entrepreneurial ideology are integrated in the model by means of the competency approach to training and assessment.